Numerical Analysis of Road Acoustic Screen - P. Stempin; W. Sumelka (Archives of Civil Engineering, 2020)
This article presents the results of a numerical analysis of the road acoustic screen deterioration. Due to the fact that road noise barriers are located in an environment of very high corrosivity, the problem is the rusting of the metal cladding of component panels. The presented case study was, therefore, verified to fulfill the requirements presented in the Eurocode EN 1794-1. Static analysis for wind load and dynamic analysis for the load induced from vehicles was carried out. The analysis presented in the article proved the design errors and their contribution to the formation of severe corrosion, as well as demonstrating the importance of dynamic analysis in the design of acoustic screens.